El financiamiento de la educación superior en Colombia: Retos y tensiones (2010)
The text addresses the problem of financing higher education in Colombia, with emphasis on the status of state universities, on the assumption that this type of education, but has high social benefits for the development of any country, it is a private good, because it is not a standard training process, analogous to primary and secondary education (which is the same for all students), but meets the interests and needs of each person, that predispose participate in the financing of the program launched. In this sense, the costs of higher education in each individual may be shared by those who benefit from it: the student, his family, society and state.